Analysis of Moral Reasoning in the Submission of Recipients of the Family Hope Program in Mazingo Tanose'o Village, Hiliduho District, Nias Regency in 2023 - Dewika Halawa; Hendrikus Otniel Nasozaro Harefa (Edumaspul: Jurnal Pendidikan, 2023)
Moral reasoning is a person's ability to weigh alternative decisions and determine the possible direction of action that must be carried out in dealing with certain social situations, and the level of development of this ability. This research is motivated by problems caused by the submission of recipients of the Family Hope Program (PKH) in the implementation process, there are deviations from government regulations and policies related to PKH during the implementation of the plan. The submission of recipients of the Family Hope Program (PKH) in Mazingo Tanose'o Village, Hiliduho District, Nias Regency has not been based on Moral Reasoning. The purpose of this study is to determine the application of moral reasoning in the application of PKH recipients, the reasons for submitting the names of PKH recipients not yet based on Moral Reasoning and the efforts made so that the application of PKH recipients does not deviate from the rules. The research method used is a qualitative research method with a descriptive approach and with a total of 9 informants. The submission of PKH recipients has been based on the application of moral reasoning, but in its implementation the Village Head only has the authority to submit data on prospective PKH recipients. Efforts made so that the submission of PKH recipients does not deviate from the rules are that the Village Facilitator or the Social Service always updates the data, the Village Facilitator routinely conducts home visits to ensure the actual situation, as a community must provide original data to the Social Service and use PKH funds specifically for children's health and education.